A Novel Severity Score Index for Febrile Neutropenic Patients with Colorectal Diseases - Camila Perazzoli; Rogério S. Parra; Marley R. Feitosa; Enrico Sfoggia; Belinda Pinto Simões; José J. R. Rocha; Omar Féres (Gastroenterology Research and Practice)
Introduction. Abdominal and anorectal disorders may be the cause of clinical decompensation in neutropenic febrile patients, particularly those with hematologic diseases. Infection is a cause for concern for the colorectal surgeon. Some conditions have few manifestations and can lead to death within a short period of time. This study presents the novel colorectal disorder severity score for febrile neutropenic patients. Materials and Methods. This was a case series study analyzing the medical records of 897 patients admitted to the Hematology and Hematopoietic Stem Cell Transplant Unit in a university hospital between the years 2008 and 2013. Seventy-four episodes of febrile neutropenia in 69 patients diagnosed with an abdominal or anorectal infection site were eligible for the study. The new scoring system proposed here is based on the author’s clinical experience and an extensive literature review. In addition to the extensive literature review, effect measures were calculated, and a statistical analysis was performed. Based on an evaluation of common biological plausibility criteria, five factors were selected as the main predictors of hospital mortality in febrile neutropenic patients with colorectal disease. Results. The proposed score demonstrated increased mortality as the condition worsened as reflected by an increasing score (Fisher’s exact test: 0.001). When considering the logistic model for the probability of death by score level, the AUC value was 0.82 (0.72-0.925), and the Hosmer-Lemeshow statistic value was 2.3, p=0.806. Conclusion. The proposed scoring system allows prediction of the likelihood of death during hospitalization for febrile neutropenic patients with an abdominal and anorectal focus. New studies on the subject are required, and the proposed scoring scale must be validated on a larger and different sample of patients.